Transcriptome and Metabolome Comparison of Smooth and Rough Citrus limon L. Peels Grown on Same Trees and Harvested in Different Seasons - Liu, Hong-ming; Long, Chun-rui; Wang, Shao-hua; Fu, Xiao-meng; Zhou, Xian-yan; Mao, Jia-mei; Yang, Hong-xia; Du, Yu-xia; Li, Jin-xue; Yue, Jian-qiang; Hu, Fa-guang (Frontiers in Plant Science, 2021)
Farmers in Yunnan (China) harvest lemon (Citrus limon L. Burm. f.) twice a year i.e., in spring and autumn, enabling them to have relatively higher profitability as compared to other lemon producing areas. The regular fruits harvested in autumn have a smooth skin. However, the lemons that are harvested in spring have a rough skin, which makes it less attractive to customers. Furthermore, it causes reduction in the commodity value and economical losses to the farmers. This study investigated the key transcriptomic and metabolomic differences in the lemon fruit peels (variety Yuning no. 1) harvested at 30, 60, 90, 120, and 150 days after flowering from the same trees in different seasons. We identified 5792, 4001, 3148, and 5287 differentially expressed genes (DEGs) between smooth peel (C) and rough peel (D) at 60, 90, 120, and 150 days after flowering, respectively. A total of 1193 metabolites differentially accumulated (DAM) between D and C. These DEGs and DAMs were enriched in MAPK and plant hormone signaling, terpenoid biosynthesis, flavonoid and phenylalanine biosynthesis, and ribosome pathways. Predominantly, in the early stages, the phytohormonal regulation and signaling was the main driving force for the changes in peel surface. The changes in the expression of genes associated with asymmetric cell division were also important observation. The biosynthesis of terpenoids was possibly reduced in the rough peels, while exclusive expression of cell wall synthesis related genes could be a possible reason of thick peels in rough skinned lemons. Additionally, cell division, cell number, hypocotyl growth, accumulation of fatty acids, lignans and coumarins related gene expression and metabolite accumulation changes were major observations. The rough and smooth peels matured in different growing seasons on the same trees are possibly due to the differential regulation of asymmetric cell division, cell number regulation, and randomization of hypocotyl growth related genes and the accumulation of terpenoids, flavonoids, fatty acids, lignans and coumarins. These results are important for increasing our understanding on the peel roughness in lemon and other citrus species.